2017
DOI: 10.3892/ijmm.2017.2897
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the proliferation, migration and angiogenic properties of human amniotic epithelial and mesenchymal stem cells and their effects on endothelial cells

Abstract: In vivo studies have shown that amnion-produced growth factors participate in many diseases that involve angiogenesis, re-epithelialization and immunomodulation. Although human amniotic epithelial cells (hAECs) and human amniotic mesenchymal stem cells (hAMSCs) can be obtained from amniotic membranes, there is little information regarding their biological differences. The aim of the present study was to isolate and characterize cells from human amnions, to investigate the biological potential and behavior of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 33 publications
1
48
0
1
Order By: Relevance
“…One of the main causes of islet death following transplant is the lack of oxygenation and nutrient supply due to disruption of the islet intrinsic microvasculature and slow revascularization in the recipient. hAECs have been shown to promote vessel formation in vitro and angiogenesis in vivo, in correlation with the expression of numerous angiogenic factors directly involved in the revascularization process, such as vascular endothelial growth factor‐A (VEGF‐A), platelet‐derived growth factor subunit B (PDGF‐B), and angiopoietin‐1 (ANGPT1) . Among these factors, the VEGF family is known to stimulate the migration of endothelial cells and improve vascular permeability .…”
Section: Discussionmentioning
confidence: 99%
“…One of the main causes of islet death following transplant is the lack of oxygenation and nutrient supply due to disruption of the islet intrinsic microvasculature and slow revascularization in the recipient. hAECs have been shown to promote vessel formation in vitro and angiogenesis in vivo, in correlation with the expression of numerous angiogenic factors directly involved in the revascularization process, such as vascular endothelial growth factor‐A (VEGF‐A), platelet‐derived growth factor subunit B (PDGF‐B), and angiopoietin‐1 (ANGPT1) . Among these factors, the VEGF family is known to stimulate the migration of endothelial cells and improve vascular permeability .…”
Section: Discussionmentioning
confidence: 99%
“…The wound-healing assay is currently used in specialized literature [61][62][63] and is chosen because performed in short times (4 and 7 hours), gap occupation by cells is exclusively due to their migration and not to their proliferation, since there is not sufficient time going to complete a cell cycle. Migration assay showed that material extracts using both 100 and 300 mg L -1 concentrations were able to increase the migratory rate of BAEC, suggesting a proangiogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the stem cells derived from term amnion possess multilineage differentiation potential [ 25 ], non-tumorigenicity [ 26 ], low immunogenic profile [ 27 ], and anti-inflammatory functions [ 28 ], reducing the risk of cell rejection and the potential of graft-versus-host disease. In addition, since hAESCs have similar pluripotent properties with embryonic stem cells, they are not associated with the ethical concerns [ 29 ]. Taken together, these observations suggest that the hAESCs might be ideal candidates for regenerative medicine and tissue repair.…”
Section: Introductionmentioning
confidence: 99%